2000
DOI: 10.1159/000010316
|View full text |Cite
|
Sign up to set email alerts
|

Use of Prostaglandin E2 for Cervical Ripening in Pregnancies with Oligohydramnios

Abstract: The effectiveness of intracervical prostaglandin E2 (PGE2) was studied in 96 primigravidas with unfavorable cervix and need for induction of labor. Group A consisted of 49 oligohydramnios and group B of 47 cases with normal amniotic fluid volume (controls). A single dose of 0.5 mg PGE2 gel was applied intracervically and several parameters were recorded during the next hours. The mean number of uterine contractions increased during the first 2 h in both groups, decreased during the next one and did not change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
2
1
Order By: Relevance
“…9 Similarly, Stefos et al in 2000 revealed no differences in mode of delivery, Apgar's scores, or rates of acidosis with PGE 2 . 11 These findings further support the efficacy and safety of PGEs in the induction for patients with oligohydramnios 9,11 and FGR. 13,14 Conversely, contrary to a recent meta-analysis, 13 our study did not demonstrate an increased rate of CD for abnormal fetal heart rate tracing in pregnancies complicated by oligohydramnios with and without FGR.…”
Section: Results In Context Of What Is Knowncontrasting
confidence: 99%
See 1 more Smart Citation
“…9 Similarly, Stefos et al in 2000 revealed no differences in mode of delivery, Apgar's scores, or rates of acidosis with PGE 2 . 11 These findings further support the efficacy and safety of PGEs in the induction for patients with oligohydramnios 9,11 and FGR. 13,14 Conversely, contrary to a recent meta-analysis, 13 our study did not demonstrate an increased rate of CD for abnormal fetal heart rate tracing in pregnancies complicated by oligohydramnios with and without FGR.…”
Section: Results In Context Of What Is Knowncontrasting
confidence: 99%
“…Prior research into the optimal method of induction for patients with fetuses affected by oligohydramnios has revealed mixed results. Rates of adverse neonatal outcomes including acidemia, Apgar <7 at 5 minutes, neonatal intensive care unit (NICU) admission and neonatal deaths were not increased with the use of either prostaglandin E1 (misoprostol) or prostaglandin E2 (dinoprostone) in multiple studies [8][9][10][11] . However the effect of prostaglandins on mode of delivery and need for cesarean for non-reassuring fetal heart rate tracings varied between studies: some show no difference in cesarean delivery (CD) rate [9][10][11][12] while others showed an increased rate of CD in patients with oligohydramnios who received prostaglandins (PGE) 8,12 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Although there are studies testing the safety and efficacy of different prostaglandin preparations such as prostaglandin E 2 for labor induction in cases with oligohydramnios [12,13], currently there is no study in the literature focusing on the efficacy and safety of misoprostol for cervical ripening and labor induction in oligohydramniotic patients. Data on the effectiveness of misoprostol are promising [7].…”
Section: Discussionmentioning
confidence: 99%